Legitimation processes of sport organizations: the case of Norwegian youth sport policy and the 2016 Lillehammer Winter Youth Olympic Games - Strittmatter, A.-M. (NIH, 2017)
Introduction: The Norwegian Olympic Committee and Confederation of Sport`s (NIF) main argument for hosting the 2016 Lillehammer Youth Olympic Games (hereafter referred to as Lillehammer 2016) was the alleged positive demonstration effect, the promise that the event would increase the active engagement of youth in Norwegian organized sports in terms of participation, young leadership, and young coaches, and play an important role in NIF`s youth sport policy. Aim: The aim of this research is to analyze how different actors shape and influence Norwegian youth sport policy in connection to Lillehammer 2016 as legitimation process of NIF. This aim was met through the examination of four research questions, which comprise the entire policy process, from formulation (Article 1) via implementation (Article 2) and perception of the policy target group (Article 3) to the policy outcome (Article 4). Theoretical framework: The combination of neo-institutional theory and implementation literature served as analytical framework for examining how structures and practices within the youth policy process and Lillehammer 2016 are expressed, implemented, reproduced, and changed.